2016
DOI: 10.3892/mmr.2016.5095
|View full text |Cite
|
Sign up to set email alerts
|

Urinary microRNA-based signature improves accuracy of detection of clinically relevant prostate cancer within the prostate-specific antigen grey zone

Abstract: At present, prostate-specific antigen (PSA) is used as a clinical biomarker for prostate cancer (PCa) diagnosis; however, a large number of patients with benign prostate hyperplasia (BPH) with PSA levels in the ʻgray areaʼ (4–10 ng/ml) are currently subjected to unnecessary biopsy due to overdiagnosis. Certain microRNAs (miRs) have been proven to be useful biomarkers, several of which are detectable in bodily fluids. The present study identified and validated a urinary miR-based signature to enhance the specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 44 publications
0
49
0
1
Order By: Relevance
“…93 Recently, it has been reported that miRNA levels in urine from PCa patients are significantly altered compared with that from benign prostate hypertrophy patients. 94 They showed that higher levels of urinary miR-100 and miR-200b were effective parameters to detect the presence of PCa with PSA levels in the gray zone. 94 Other investigators identified miR-205, -214, -1825 and -484 as potential urinary biomarkers for PCa diagnosis.…”
Section: Mirnas As Predictive Biomarkers In Pcamentioning
confidence: 98%
See 1 more Smart Citation
“…93 Recently, it has been reported that miRNA levels in urine from PCa patients are significantly altered compared with that from benign prostate hypertrophy patients. 94 They showed that higher levels of urinary miR-100 and miR-200b were effective parameters to detect the presence of PCa with PSA levels in the gray zone. 94 Other investigators identified miR-205, -214, -1825 and -484 as potential urinary biomarkers for PCa diagnosis.…”
Section: Mirnas As Predictive Biomarkers In Pcamentioning
confidence: 98%
“…94 They showed that higher levels of urinary miR-100 and miR-200b were effective parameters to detect the presence of PCa with PSA levels in the gray zone. 94 Other investigators identified miR-205, -214, -1825 and -484 as potential urinary biomarkers for PCa diagnosis. 95,96 At present, no reports describe association of urinary miRNA levels and risk of CRPC.…”
Section: Mirnas As Predictive Biomarkers In Pcamentioning
confidence: 98%
“…Preliminary results suggest that the measurement of urinary miRNAs may be valuable as biomarkers in the management of patients with early PCa, although conclusions of the available studies are based on a short series of patients [62]. Recently, Salido-Guadarrama et al [66] identified a miR-100/200b signature in the urine obtained after prostate massage comparing 73 patients with high-risk PCa and 70 patients with BPH. The AUC for this signature (0.738) was higher than the obtained AUCs for total PSA (0.681) and %fPSA (0.710).…”
Section: Mirnasmentioning
confidence: 99%
“…Interestingly, miRNAs have also been found in virtually all biological fluids, including cerebrospinal fluid, tears, saliva, breast milk, amniotic fluid, urine, as well as feces [38][39][40][41][42] …”
Section: Mirna Expression Regulation and Stabilitymentioning
confidence: 99%